An Exploration of Human Identity in the Post humanist World: A Reading on Max Barry’s Machine Man - T.P. Aishwarya (ILN Journal: Indian Literary Narratives, 2024)
This study attempts to analyse how the emerging concept of posthumanism is a threat to human identity. In an era characterised by rapid technological advancements, posthumanism surpasses anthropocentric approaches in challenging humanised notions and perspectives, leaving threats on erasures of human innate identities. To cope with the emerging world, human beings transform themselves physically, ethically, and emotionally. This paper delves into the multifaceted terrain of posthumanism, exploring its theoretical underpinnings, cultural manifestations, and implications for human beings’ collective future. It also embarks on a comprehensive exploration of identity erasure within the context of posthumanism, dissecting the complex interplay between technology and human subjectivity.